Long‐term Survival of Straumann Dental Implants with TPS Surfaces: A Retrospective Study with a Follow‐up of 12 to 23 Years. (23rd March 2015) - Becker, Stephan T.; Beck‐Broichsitter, Benedicta E.; Rossmann, Christian M.; Behrens, Eleonore; Jochens, Arne; Wiltfang, Jörg
Abstract: Purpose: The aim of this study was to evaluate the long‐term dental implant survival rates of Straumann dental implants in a university hospital environment over 12 to 23 years. Materials and Methods: A total of 388 Straumann dental implants with titanium‐sprayed surfaces (TPS) were inserted in 92 patients between 1988 and 1999 in the Department of Oral and Maxillofacial Surgery of the University Hospital Schleswig‐Holstein in Kiel, and they were reevaluated with standardized clinical and radiological exams. Kaplan–Meier analyses were performed for individual factors. Cox proportional hazard regression analysis was used to detect the factors influencing long‐term implant failure. Results: The long‐term implant survival rate was 88.03% after an observation time of 12.2 to 23.5 years. Cox regression revealed statistically significant influences of the International Team for Implantology (ITI) implantation type ( p  = .00354) and tobacco smoking ( p  = .01264) on implant failure. A proportion 82.8% of the patients with implant losses had a medical history of periodontitis. Peri‐implantitis was diagnosed in 9.7% of the remaining implants in the long‐term survey. Conclusions: This study emphasized the long‐term rehabilitation capabilities of Straumann dental implants in complex cases. The survival rates after several years constitute important information for patients, as well as for clinicians, in deciding about different concepts of tooth replacement. Patient‐related and technical factors – determined before implant placement – could help to predict the risk of implant loss.